THE LEXICO-SEMANTIC GROUP OF ADJECTIVES DENOTING PERSONAL QUALITIES IN CONTEMPORARY RUSSIAN (Journal of Foreign Language Studies, 2025)
This article investigates the structure of adjectives within the lexico-semantic group denoting personal qualities in contemporary Russian. It identifies the core semantic features of these adjectives as well as their typical syntagmatic characteristics. This study draws on illustrative materials collected through targeted continuous sampling and employs linguistic observation, comparative analysis of linguistic units, contextual analysis, and stylistic interpretation of adjectives within specific semantic models. In certain cases, componential analysis and dictionary-based research were also applied. The focus on adjectives denoting personal qualities is well justified, given their categorical nature and inherent capacity to ‘color’ representations of the objective world. Moreover, the descriptive and evaluative functions of adjectives are often inseparable, which is vital in constructing character portraits. This group of adjectives serves as a powerful and concise tool for describing individuals or fictional characters, contributing to more vivid and expressive portrayals.
Keywords: lexico-semantic group of adjectives; personal qualities; core semantic features; syntagmatic characteristics; potrayal tools